2008
DOI: 10.1038/jcbfm.2008.50
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Expression of Toll-Like Receptor 4 in Monocytes Correlates with Severity of Acute Cerebral Infarction

Abstract: In the present study, we observed the expression of toll-like receptor 4 (TLR4) and its downstream signal pathway in peripheral blood monocytes (PBMs) from patients with acute cerebral infarct (ACI). The expression of TLR4 and MyD88 by PBMs was determined by flow cytometry and reverse transcriptase-polymerase chain reaction, and nuclear factor-jB (NF-jB) activity was detected by electrophoretic mobility shift assay. Ischemia/reperfusion injury-induced cerebral edema, infarction area, and neurologic impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 36 publications
4
79
1
Order By: Relevance
“…Earlier studies have shown that poor outcome after stroke is associated with innate responses signaled through TLR4 in monocytes (Urra et al, 2009a;Yang et al, 2008). In this study, the expression of TLR4 disclosed no significant differences between monocyte subtypes, suggesting that other differences in monocyte subtypes affect stroke outcome.…”
Section: Figurecontrasting
confidence: 41%
See 1 more Smart Citation
“…Earlier studies have shown that poor outcome after stroke is associated with innate responses signaled through TLR4 in monocytes (Urra et al, 2009a;Yang et al, 2008). In this study, the expression of TLR4 disclosed no significant differences between monocyte subtypes, suggesting that other differences in monocyte subtypes affect stroke outcome.…”
Section: Figurecontrasting
confidence: 41%
“…Stroke may also induce monocyte deactivation, which is characterized by decreased HLA-DR expression and impaired production of proinflammatory cytokines on stimulation with lipopolysaccharide (Emsley et al, 2007;Haeusler et al, 2008). A higher expression of Toll-like receptor (TLR)4 in monocytes of patients with acute stroke was recently associated with poor prognosis (Urra et al, 2009a;Yang et al, 2008), in agreement with experimental data showing that TLR4-deficient mice have minor infarctions and less inflammatory response after an ischemic insult (Caso et al, 2007).…”
Section: Introductionmentioning
confidence: 61%
“…However, these studies were conducted using recombinant proteins (Lasarte et al, 2007) or selected serum (Yang et al, 2008), instead of a pool of serum from ischemic stroke patients. Besides, they have used transformed cells instead of cells from human origin.…”
Section: Discussionmentioning
confidence: 99%
“…During the preparation of the manuscript, a work has been published 43 showing an increase in circulating TLR4 ϩ monocytes in a group of 19 patients with acute ischemic stroke. Moreover, the expression of TLR4 correlated with stroke severity at 10 days.…”
Section: Disclosuresmentioning
confidence: 99%